Peningkatan Hasil Belajar Siswa dengan Metode PBL Berbantuan Diskusi Kelompok pada Materi Sengsara dan Wafat Yesus Fase E Kelas X SMKN 7 Surakarta - Lusius Supriyatno; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve students' motivation and learning outcomes by using the Problem Based Learning (PBL) learning method assisted by group discussions on the material of the Passion and Death of Jesus in the subject of Catholic Religious Education. The subjects of this study were 7 students of class X of the DKV Department of SMKN 7 Surakarta in the 2024-2025 academic year in the even semester with 2 cycles. Each cycle is carried out in 1 meeting for 2 teaching hours. Each meeting includes the stages of planning, action, observation and reflection. Data collection techniques are carried out through documentation, observation sheets, group work results and written tests. Based on the research conducted, it was concluded that this method is very effective in improving student learning outcomes. This is indicated by the increasing activeness of students in doing assignments. Based on the researcher's observations in cycle 1, there were 3 children (43%) who paid less attention during learning, were less active in discussions and tended to discuss things that were not related to the lesson. As many as 57% were actively involved and focused on the tasks given. In cycle 2, student activity increased. Only 1 student (14%) still looks less active. An increase of 29%, from the original 57% to 86%. The increase in learning outcomes can also be seen from the summative test scores at the end of learning. In cycle 1 of 7 students only 4 children scored above 85 (57%) and experienced an increase in cycle 2 to 86% (6 children).